2018
DOI: 10.1038/s41431-017-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, experiences and attitudes concerning genetics among retinoblastoma survivors and parents

Abstract: Clinical genetic services are increasingly providing a more nuanced understanding of genetic disease diagnostics and future risk for patients. Effectively conveying genetic information is essential for patients to make informed decisions. This is especially important for survivors of heritable cancers such as retinoblastoma (childhood eye cancer), where survivors who carry a germline mutation in the RB1 gene are at increased risk of second cancers in adulthood, and of passing on the disease risk to future offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 32 publications
(37 reference statements)
1
44
0
3
Order By: Relevance
“…People affected by retinoblastoma have indicated that they are deeply incentivized to keep abreast of research and help co-create it. 2 Parents want better outcomes for their children as they grow older and start families of their own, and survivors want research focused on preventing retinoblastoma, given that it can be predicted in familial cases. 2 As the retinoblastoma team at The Hospital for Sick Children, we noticed patients' interest in becoming more deeply involved in research but recognized that there was little opportunity for such involvement.…”
Section: Researcher and Clinician Perspective: Engaging Patients In Rmentioning
confidence: 99%
See 3 more Smart Citations
“…People affected by retinoblastoma have indicated that they are deeply incentivized to keep abreast of research and help co-create it. 2 Parents want better outcomes for their children as they grow older and start families of their own, and survivors want research focused on preventing retinoblastoma, given that it can be predicted in familial cases. 2 As the retinoblastoma team at The Hospital for Sick Children, we noticed patients' interest in becoming more deeply involved in research but recognized that there was little opportunity for such involvement.…”
Section: Researcher and Clinician Perspective: Engaging Patients In Rmentioning
confidence: 99%
“…2 Parents want better outcomes for their children as they grow older and start families of their own, and survivors want research focused on preventing retinoblastoma, given that it can be predicted in familial cases. 2 As the retinoblastoma team at The Hospital for Sick Children, we noticed patients' interest in becoming more deeply involved in research but recognized that there was little opportunity for such involvement. Ms Baddeliyanage and Dr Shaikh wrote sections of the manuscript and reviewed the finalized manuscript; Dr Dimaras conceptualized the manuscript, wrote a section of the manuscript, and reviewed the manuscript; Ms White conceptualized the manuscript, synthesized the patient, medical, and research perspectives to write the initial manuscript, and revised the manuscript; and all authors approved the final manuscript as submitted and agree to be accountable for all aspects of the work.…”
Section: Researcher and Clinician Perspective: Engaging Patients In Rmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of studies on parental awareness have concentrated on the subset of familial retinoblastoma patients and consistently found that raised awareness improved early diagnosis and outcome [11,12]. More recently, a qualitative study from Canada explored knowledge of retinoblastoma genetics among retinoblastoma survivors and parents of children with retinoblastoma, and it revealed that knowledge of retinoblastoma genetics was variable and often limited [13]. To our knowledge, this was the first study analyzing parent knowledge on retinoblastoma of both heritable and nonheritable forms.…”
Section: Discussionmentioning
confidence: 96%